Pochodzenie i poczucie wspólnoty regionalnej wśród mnichów na Pustyni Judzkiej w V i VI wieku – na podstawie Żywotów mnichów palestyńskich Cyryla ze Scytopolis - Twardowska, Kamilla (In Gremium. Studies in History, Culture and Politics, 2013)
Origin and the sense of regional community among monks in Judaean Desert in the 5th and 6th century – based on ‘The lives of Palestinian monks’ by Cyril of Scythopolis The work by Cyril of Scythopolis titled ‘The lives of the Monks of Palestine’ is an irreplaceable source of knowledge to reveal a range of aspects connected with the beginning and flourishing of monasticism in the Judaean Desert. Palestinian monasticism, multi-ethnic in its source, managed to preserve its cosmopolitism at the time of its greatest development that took place in the 6th century. Monks came from the area of the whole Empire, however among the monks in the Judaean Desert, there dominated those who derived from Asia Minor and other areas of the eastern part of the Empire. We easily notice both regional and family bonds among them.